4CPS-210 A 1- to 2-year follow-up of treatment prescribed to obese patients: evolution of treatments and vitamin supplementations in patients who underwent sleeve gastrectomy. (2nd March 2018) - Roseau, C; Henry, C; Paret, A; Decottignies, A; Rieutord, A; Roy, S
Abstract : Background: Laparoscopic sleeve gastrectomy (LSG) has become the most used bariatric surgery technique in western countries because of a better-assumed balance between weight loss, reduction of comorbidity and vitamin deficiency. Purpose: We present 1- to 2 year follow-up results regarding the consequences of treatments of obesity-related comorbidities, the weight loss and the development of vitamin insufficiencies from a single centre. Material and methods: In this retrospective study, eligible patients were those who underwent LSG in 2014 and had medication reconciliation before surgery. Included patients were those with 1- and 2 year-follow up results. Pre-operative obesity-related treatments were collected from medication reconciliations: post-operative treatments were collected from hospitalisation follow-up reports. Results: Two hundred and forty-one patients were eligible, and 97 were included. The initial medium body mass index was 42.3 kg/m² before surgery, 30.5 kg/m² after 1 year and remained steady at 30.5 kg/m² after 2 years. Medium weight was 117.2 (±18.4) kg before surgery and 84.5 (±16.5) after 1 year, 84.4 (±16.6) kg after 2 years. The average number of treatments went from 1.9 (±1.9) to 1 (±0.9) 1 year after LSG and to 0.9 (±1.2) after 2 years. Improvement of obesity-related treatments are presented in Table 1. Regarding vitamin insufficiency, 54.6% of the patients had developed a deficiency in B9, 10.3% in B12% and 45.4% in at least one other vitamin deficiency within 2 years. Table 1. Number of patients presenting at least one line of treatment reduction at 1 year and 2 years Conclusion: This study is consistent with present LSG data regarding comorbidity improvement. We were able to show that LSG is very efficient in most of the comorbidity, although a few patients had a gastro-esophageal reflux (GERD) improvement overall. We also pointed out that vitamin deficiencies are often discovered, in spite of a good tolerance of LSG overall. No conflict of interest